2019
DOI: 10.1017/s1368980019001447
|View full text |Cite
|
Sign up to set email alerts
|

Eating habits and weight status in Finnish adolescents

Abstract: Objective:To investigate the association between eating habits and weight status in adolescents in Finland.Design:Cross-sectional study.Setting:The Finnish Health in Teens (Fin-HIT) study is a cohort study conducted in adolescents attending third to sixth grade in 496 schools in forty-four municipalities in Southern, Middle and Northern Finland in 2011–2014.Participants:Analyses included 10 569 adolescents from the Fin-HIT study aged 9–14 years (5005 boys and 5564 girls). Adolescents were categorized by their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 42 publications
3
12
0
1
Order By: Relevance
“…Previously, we have linked irregular breakfast to excess weight in Finnish adolescents (Viljakainen et al, 2019). There is strong evidence of an association between an irregular breakfast pattern and overweight and obesity in European children and adolescents (Szajewska and Ruszczynski, 2010;Viljakainen et al, 2019).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Previously, we have linked irregular breakfast to excess weight in Finnish adolescents (Viljakainen et al, 2019). There is strong evidence of an association between an irregular breakfast pattern and overweight and obesity in European children and adolescents (Szajewska and Ruszczynski, 2010;Viljakainen et al, 2019).…”
Section: Discussionmentioning
confidence: 95%
“…Adolescents filled in a web-based baseline questionnaire, including eating habits and breakfast and dinner patterns on an electronic tablet in school (de Oliveira Figueiredo et al, 2019;Figueiredo et al, 2019;Viljakainen et al, 2019). In addition, participants provided an unstimulated saliva sample, and trained fieldworkers measured their height and weight in a standardized way (Figueiredo et al, 2019) which we used to calculate body mass index (BMI) (kg/m 2 ), described in detail elsewhere (Sarkkola et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, in our study we did see that there is a significant relationship between students success and their status as per meal-skipping, with students skipping meals performing lower in terms of TEOG scores. Recently, Viljakainen and colleagues showed that avoiding fruits and vegetables and following irregular breakfast and dinner patterns were all associated with underweight or excess weight in Finnish adolescents [22]. Hence, their work illustrated that optimal weight achievement is more difficult and less likely among adolescent with poor dietary habits.…”
Section: Discussionmentioning
confidence: 99%